Pop Up Book Cerita Rakyat Sebagai Sarana Literasi untuk Anak-Anak Sanggar Genius Ar Rasyid dengan Teknik Read Aloud - Mimi Rosadi; Rohayati Sihotang; Rotua Situmorang; Roymantini Novita Sari Sihite; Risky Kurniawan; Rut Yesni Sianturi; Saida Putri Mei Purba (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
In the midst of efforts to build a literacy culture, Sanggar Genius Ar Rasyid has actually become a warm space for children to learn and grow. However, the post-pandemic reality shows a significant decline in their interest in reading. Children began to visit rarely. The atmosphere of reading becomes monotonous, activities feel less interesting, and the available facilities are not able to provoke their curiosity. Many of them feel bored, and the spirit of literacy is slowly fading. Seeing this condition, there is an awareness that children need something more than just books and ordinary reading. They need a touch of imagination, color, and lively engagement. So, the solution offered is to present Pop-Up Book media with the theme of folklore, combined with the read aloud technique, a way of reading stories that bring words to life through intonation, expression, and warm interaction. Training on making Pop-Up Books for studio administrators is also the starting point for change. The results were encouraging: the creativity of the administrators increased, fresh ideas popped up, and most importantly, the children were excited again. They not only read, but also hear, imagine, remember, and share stories together. The reading aloud technique makes reading moments more personal, builds closeness, and fosters a sense of love for books. Now, reading is no longer a boring activity.